Bluetongue virus: Past, present, and future scope - Subhra Subhadra; Daggupati Sreenivasulu; Ritesh Pattnaik; Basant Kumar Panda; Subrat Kumar (Journal of Infection in Developing Countries)
Bluetongue (BT), once considered a disease of sheep confined to the southern African region, has spread all over the world. BT is a viral disease caused by the bluetongue virus (BTV). BT is regarded as an economically important disease in ruminants of compulsory notification to OIE. BTV is transmitted by the bite of Culicoides species. Research over the years has led to a better understanding of the disease, the nature of the virus life cycle between ruminants and Culicoides species, and its distribution in different geographical regions. Advances have also been made in understanding the molecular structure and function of the virus, the biology of the Culicoides species, its ability to transmit the disease, and the persistence of the virus inside the Culicoides and the mammalian hosts. Global climate change has enabled the colonization of new habitats and the spread of the virus into additional species of the Culicoides vector. This review highlights some of the current findings on the status of BT in the world based on the latest research on disease aspects, virus-host-vector interactions, and the different diagnostic approaches and control strategies available for BTV.